PERBEDAAN KUALITAS TIDUR SETELAH MENGONSUMSI BERBAGAI JENIS MINUMAN KOPI PADA USIA DEWASA - Triantara, Adhitya Nugraha; Widyastuti, Hartanti Sandi (Journal of Nutrition College, 2017)
Background: Coffee is categorized as psychostimulant drinks. The content of caffeine in coffee affects the increase in dopamine levels in the brain and one of the caffeine functions was a stimulant for the central nervous system. Caffeine consumption can also increased adrenaline and blood pressure. This can cause negative effects when consumed in excessive amount (> 400mg / day) such as anxiety, fatigue when woke up the morning. Sleep disorders and poor sleep quality.Objectives : Found the difference of caffeine content in various types of coffee drink and found the difference in sleep quality after consumed various types of coffee drinks..Method: The study design was Cross-Sectional with 54 adults around age 18-25 years as subjects. Subjects were divided into three groups, those who consumed espresso coffee, cappuccino, and café latte. The sleep quality of subjects was measured using the Pittsburg Sleep Quality Index. The caffeine content of espresso coffee, cappuccino, and café latte is tested using UV-Vis Spectrophotometry. Normality test using Kolmogorov Smirnov test (n> 50). Bivariate analysis using the Wilcoxon and Kruskal-Wallis tests.Results: Espresso coffee drinks has a caffeine content of 182.4 mg/cup, cappuccino coffee drinks has a caffeine content of 54 mg/cup, and café latte coffee drinks has a caffeine content of 41.25 mg/cup. The result of bivariate test showed that there was a significant difference in sleep quality after coffee consumption in the three subject groups. Subjects who consumed espresso coffee drink had a sleep quality that tends to be worse compared to subjects who consumed cappuccino and café latte.Conclusion: The study found differences in caffeine levels in espresso, cappuccino and café latte and the study also found a significant difference in sleep quality after consumed various types of coffee drinks. Subjects in the espresso coffee drink group had the worst sleep quality.